Cervical thymic cyst - A rare diagnosis - Jayateertha Joshi; Abhishek Ganguly; Chaithra G Ventakataramana; Sadashiva P Rao (Wolters Kluwer Medknow Publications, 2022)
Cervical thymic cysts are rare cysts which are seen in the first decade of life in males on the left side. The following is a case of a young female with a painless swelling on the right side of the neck. She was evaluated and underwent exploration of the neck and excision of the swelling.